The morphology of the immature stages of two rare Lixus species (Coleoptera, Curculionidae, Lixinae) and notes on their biology - Trnka, Filip; Stejskal, Robert; Skuhrovec, Jiří (ZooKeys, 2016)
The mature larvae and pupae of Lixus (Ortholixus) bituberculatus Smreczyński, 1968 and Lixus (Dilixellus) neglectus Fremuth, 1983 (Curculionidae: Lixinae: Lixini) are described and compared with known larvae of 21 other Lixus and 2 Hypolixus taxa. The mature larva and pupa of Lixus bituberculatus are the first immature stages described representing the subgenus Ortholixus. The larva of Lixus neglectus, in the subgenus Dilixellus, is distinguished from the known larvae of four species in this subgenus by having more pigmented sclerites on the larval body. All descriptions of mature larvae from the tribe Lixini, as do all known species from the tribe Cleonini, fit the diagnosis of the mature larva of the Lixinae subfamily. Furthermore, new biological information of these species in the Czech Republic, Slovakia and Romania is provided. For Lixus bituberculatus, a chicory, Cichorium intybus L. (Asteraceae), is identified as a host plant, and Lixus neglectus is found on dock Rumex thyrsiflorus Fingerh. (Polygonaceae). Both species are probably monophagous or oligophagous. Adults of Lixus bituberculatus often inhabit host plants growing in active, dry and sunny pastures with sparse patches without vegetation, being mostly active during the night in April/May and then again in September, when the highest activity levels are observed. Adults of Lixus neglectus inhabit dry grasslands on sandy soils with host plants, being active during the day from May to September, with the highest level of activity in May/June and September. The larvae of both species are borers in the stem and root of the host plant, and they pupate in root or root neck. Adults leave the pupation cells at the end of summer and do not hibernate in the host plants. Finally, Romania is a new geographic record for Lixus bituberculatus.
Keywords: Cichorium intybus; host plant; mature larva; Central Europe; larval development; pupa; life cycle; Weevil; Rumex thyrsiflorus; Palaearctic region